2002
DOI: 10.1089/15258160260194866
|View full text |Cite
|
Sign up to set email alerts
|

Strong Public Support for Treatment and Research Using Fetal Tissue, Particularly Among Those Accepting the Scientific World-View

Abstract: Data from four large representative national sample surveys in Australia between 1993 and 2000 show strong public support for treatment using fetal tissue. Support remains high even if the treatment has only a remote chance of success, or if the goal is research rather than treatment. Regression analysis reveals striking new evidence on the links between science and moral beliefs. Even adjusting for religious denomination and numerous demographic characteristics, acceptance of evolution and of aspects of astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The socio-demographic factors are, for the most part, not statistically signifi cant, as has also been found in previous studies of other bioethical attitudes such as view on the morality of stem cell research [37] and research using different questions on attitudes towards abortion [9,34] . The only systematically signifi cant socio-demographic variable is sex, with men being 6-9 points out of 100 more favourable than women towards all aspects of GLGT.…”
Section: Social Differences In Attitudes Towards Glgt and Abortionsupporting
confidence: 56%
See 3 more Smart Citations
“…The socio-demographic factors are, for the most part, not statistically signifi cant, as has also been found in previous studies of other bioethical attitudes such as view on the morality of stem cell research [37] and research using different questions on attitudes towards abortion [9,34] . The only systematically signifi cant socio-demographic variable is sex, with men being 6-9 points out of 100 more favourable than women towards all aspects of GLGT.…”
Section: Social Differences In Attitudes Towards Glgt and Abortionsupporting
confidence: 56%
“…For example, in the case of using fetal stem cells, public attitudes focus on the morality of the procedure per se and are only weakly infl uenced by the seriousness of the condition being treated [37] , so the seriousness gradient discovered here cannot be taken for granted for other conditions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent empirical research has found however, that religious beliefs may not be as important in the formation of public support for stem cell research as the media debate would suggest. Although peer reviewed research examining the underlying reasons for public approval of stem cell research is scant, there is some evidence that opposition is dependent upon the context of the research, and the level of trust in scientists, as well as religious beliefs (Critchley and Turney, 2004;Evans et al, 2002). This research attempts to further explore whether or not approval of stem cell research is contingent upon where the research is being conducted, who is conducting the research and why.…”
Section: Introductionmentioning
confidence: 99%